THE LIFE HISTORY AND FEEDING HABITS OF A TRIPOD FISH (TRIACANTHUS :aREVIROSTRIS TEMM.& SCHLEG.) OF THE INDIAN SEA - Dr. M.D. K. KUTHALINGAM,M. Sc., Ph. D., F. A.Z (Research Center for Biology, 1959)
abstract not available